Increasing Regional Income: Analysis Of The Effectiveness Of Market Levy Receipt In Sidoarjo Regency - Musfitaningsih, Dian; Zakkiyah, Rahayu Dewi (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Market retribution is a crucial component of regional income, playing an important role in supporting development and public services. As the primary source of income from regional financial potential, market retribution in Sidoarjo Regency successfully exceeded targets from 2019 to 2023, with the exception of 2023. This success contributes to the increase in regional original income, supports the implementation of regional autonomy, and has the potential to become an additional source of income. This study aims to analyze the effectiveness of market retribution revenue in Sidoarjo Regency, as well as identify challenges and strategies related to market service retribution. Using a qualitative descriptive analysis method, this study evaluates the target data and realization of market retribution revenue during the 2019-2023 period. The research findings indicate a very high level of effectiveness from 2019 to 2023, except for 2023.